Fbxo4-mediated degradation of Fxr1 suppresses tumorigenesis in head and neck squamous cell carcinoma - Shuo Qie (Nature Portfolio, 2017)
Fbxo4 tumour suppressor is part of a SCF E3 ligase which has two known substrates. Here, the authors identify Fxr1 as a substrate of SCFFbxo4 and identify an inherent regulatory feedback loop in head and neck squamous cell carcinoma that results in the bypass of senescence and neoplastic progression.